The role and the influence of internal audit in the public sector - Vesić Tamara; Jevtić Dalibor (Trendovi u Poslovanju)
Through the paper we have confirmed the basic hypothesis that internal audit is the key element of the financial management and control system in the public sector. The subject of this paper is to investigate the role of internal audit in the public sector, as well as to define the role and importance of internal audit in risk management in the public sector. The spreadsheet also shows the relationship of goals, risks and controls and a descriptive analysis of the recommendations regarding the final statement of the budget of the Republic of Serbia for 2018 presented at the end of the paper. It is known that in our country the occurrence of financial fraud is more and more frequent, and the audit is of great importance, because its role is to detect irregularities if there has been a misuse of public funds, wasteful and inefficient use of available budgetary resources. The audit of the Serbian budget pointed to very serious problems and revealed the irresponsibility of organizations and individuals in spending money, and it is necessary to insist on a thorough and independent audit of the financial statements of both economic associations and the state budget.